MEMETAKAN LANSKAP PENGETAHUAN: ANALISIS BIBLIOMETRIK TENTANG KETAHANAN KEUANGAN PADA UMKM - Himmah, Ika Faiqotul; Yuhertiana, Indrawati (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have an important role in financial resilience through business strategies. The purpose of this study is to analyze research developments using bibliometric analysis that maps research in the Google Scholar database from 2020 to 2024. After the selection process, 99 articles were obtained and processed using the Publish or Perish and VosViewer software. The study results showed 4 clusters that explained various business strategies, the relationship between financial resilience, business resilience with MSME business performance in the future, and MSME sustainability strategies in the modern era. The mapping results also show that business strategies for financial resilience are still a hot topic for research. Therefore, this study is expected to increase the insight and knowledge of the public regarding the right business strategy.